PENGARUH ELECTRONIC WORD OF MOUTH DI TIKTOK TERHADAP PURCHASE DECISION DAN CUSTOMER SATISFACTION MELALUI BRAND TRUST (Studi pada Konsumen Starbucks di Kota Semarang) (Faculty of Economics and Business Diponegoro University, 2023)
ABSTRACT The rapid development of today's technology, resulting in the growth of the number of social media users. With the increase in social media users, E-WOM in the current era has become the most commonly used medium for sharing and exchanging information about various products from a brand. These developments require companies to convince customers in making purchasing decisions for the goods sold. Related to this, the purpose of this study was to analyze the effect of E-WOM on purchasing decision making and customer satisfaction through brand trust in Starbucks consumers in Semarang City. The population in this study are Starbucks consumers in Semarang City, who actively use social media TikTok. The research sample used was a total of 110 respondents and the sample was collected using the purposive sampling method and then the data would be processed using SPSS 21 and AMOS 24. The results of the study show that E-WOM has a positive and significant effect on Brand Trust, and then Brand Trust has a positive and significant effect on Purchase Decision and Customer Satisfaction.